Chorioretinal neovascular membranes complicating contusional eye injuries with indirect choroidal ruptures. - Wood, C M (1990)
Chorioretinal neovascular membranes are a recognised but rare cause of late visual loss in eyes suffering contusional injuries. A series of eight cases is presented all with indirect choroidal ruptures involving the perifoveal region. Two main patterns of 'at risk' rupture were noted: a temporally situated rupture passing almost directly through the fovea, and a rupture which curves inferior or superior to the optic disc stopping just short of the fovea. In six of eight cases there was only a partial thickness rupture of the choroid. These neovascular membranes may present at any time after the original injury, either early (within six months of the injury), which could be related to persistence of the normal reparative neovascular response, or late (at least one year after the injury), which are more likely to have resulted from a secondary breakdown of the outer blood-retina barrier.